The Phytoestrogen Genistein Produces Similar Effects as 17β-Estradiol on Anxiety-Like Behavior in Rats at 12 Weeks after Ovariectomy. - Rodríguez-Landa, Juan Francisco; Cueto-Escobedo, Jonathan; Puga-Olguín, Abraham; Rivadeneyra-Domínguez, Eduardo; Bernal-Morales, Blandina; Herrera-Huerta, Emma Virginia; Santos-Torres, Andrea (BioMed Research International, 2017)
The phytoestrogen genistein produces anxiolytic-like effects in ovariectomized rats, which highlights its potential therapeutic effect in ameliorating anxiety in surgical menopausal women. However, no studies have directly compared the effects of identical doses of genistein and 17β-estradiol, the main estrogen used in hormone replacement therapy in menopausal women. The present study evaluated the anxiolytic-like effects of identical doses of genistein and 17β-estradiol (0.045, 0.09, and 0.18 mg/kg/7 days, s.c.) in a surgical menopause model in rats in the elevated plus maze and locomotor activity tests at 12 weeks after ovariectomy. Additionally, the participation of estrogen receptor-β in the anxiolytic-like effect of genistein and 17β-estradiol was explored by previous administration of the 5 mg/kg tamoxifen antagonist. Genistein and 17β-estradiol (0.09 and 0.18 mg/kg) similarly reduced anxiety-like behavior in the elevated plus maze and also increased the time spent grooming and rearing, without affecting crossing in locomotor activity test. These effects were blocked by tamoxifen. Present results indicate that the phytoestrogen genistein has a similar behavioral profile as 17β-estradiol in rats at 12 weeks after ovariectomy through action at the estrogen receptor-β. Thus genistein has potential for reducing anxiety-like behavior associated with low concentrations of ovarian hormones, which normally occurs during natural and surgical menopause.